LEADERSHIP COMMUNICATION PATTERNS IN INCREASING THE WORK MOTIVATION OF BANANA FARMERS (CASE STUDY: BANANA FARMING AT MA'HAD AL-ZAYTUN) - Tasya Kamilah, Shafa; Safitri, Wiena; N. Abdurrazaq, Muhammad (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2024)
This research was conducted at the Ma'had Al-Zaytun (MAZ) banana plantation to examine the communication patterns between banana farmers and MAZ leaders and the type of followership of banana plantation workers. This research utilizes a qualitative method, emphasizing in-depth and detailed observations. Data was collected through interviews, observation, and documentation of the agricultural and plantation division team, project leaders, and banana plantation workers. The results indicate that the communication pattern between leaders and banana farmers reflects a combination of linear and wheel patterns. This combined pattern can improve good communication between leaders and other members. This communication pattern can also increase motivation for banana plantation workers. With support and motivation from the leadership, banana plantation workers remain enthusiastic about carrying out their duties while in the banana fields. Leadership in the MAZ banana land is transformational, while the visible followership is of the implementer and partner type.